1992
DOI: 10.1007/bf00687123
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival following treatment of hepatocellular carcinoma in Singapore: evaluation of Wellferon in the prophylaxis of high-risk pre-cancerous conditions

Abstract: The present paper reviews several studies performed between 1977 and 1986 in Singapore on the 10-year survival outcome of treatment for stage I and II hepatocellular carcinoma (HCC). Of 801 HCC patients evaluated, only 2 survivors (0.3%) remained in complete remission for 13 and 14 years, respectively. One had received four weekly cycles of prednisolone, Adriamycin, vincristine and 5-fluorouracil for an inoperable HCC with a 10-cm diameter, and the other had received localised synchronised hepatic irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…7 Perhaps the most important finding of the present study is that the incidence of HCC development was significantly reduced in the IFN-treated patients. Similar to the observation in patients with hepatitis C virus and cirrhosis, 12,14-17 a beneficial effect of IFN therapy on the prevention of HCC in HBV patients with cirrhosis was observed in a few nonrandomized controlled studies, [11][12][13] which could be biased because the untreated patients might have more advanced disease and thus not be suitable or contraindicated for IFN therapy. 14 To the best of our knowledge, this could be the first randomized controlled study that shows that IFN therapy reduces HCC development in HBV patients with or without cirrhosis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…7 Perhaps the most important finding of the present study is that the incidence of HCC development was significantly reduced in the IFN-treated patients. Similar to the observation in patients with hepatitis C virus and cirrhosis, 12,14-17 a beneficial effect of IFN therapy on the prevention of HCC in HBV patients with cirrhosis was observed in a few nonrandomized controlled studies, [11][12][13] which could be biased because the untreated patients might have more advanced disease and thus not be suitable or contraindicated for IFN therapy. 14 To the best of our knowledge, this could be the first randomized controlled study that shows that IFN therapy reduces HCC development in HBV patients with or without cirrhosis.…”
Section: Discussionmentioning
confidence: 59%
“…5,6 However, long-term follow-up data are limited. [7][8][9][10] Although several studies have suggested that IFN therapy may reduce the risk of HCC in patients with HBV or hepatitis C virus-related cirrhosis, [11][12][13][14][15][16][17] evidence derived from randomized controlled studies is still lacking. Therefore, the effect of IFN on the prevention of HCC in patients with chronic HBV infection still remains to be clarified or confirmed.…”
Section: Shi-ming Lin I-shyan Sheen Rong-nan Chien Chia-ming Chu mentioning
confidence: 99%
“…Soon after trial approval, the protocol was amended to use IFN-␣2b (Intron A; Schering-Plough, Kenilworth, NJ) rather than lymphoblastoid IFN-␣. 16,17 In the treatment arm, IFN-␣ was started within 6 weeks of surgery and was given subcutaneously (3 million units 3 times every week for 48 weeks). Adverse events during treatment were rated as mild, moderate, severe, or life-threatening as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…In 1995, a small randomized controlled trial (RCT) of IFN treatment showed a decrease in the incidence of HCC in patients with hepatitis C virus (HCV) cirrhosis compared with that in untreated controls [25]. Following this study, several others, including controlled trials [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42], have been performed, mostly in patients with HCV infection. Other retrospective cohort studies of a relatively small size have shown a marked degree of heterogeneity, making it difficult to assess the actual level of benefit obtained by IFN treatment.…”
Section: Lessons From Primary Prevention Of Hcc By Ifnmentioning
confidence: 99%